Military modeling for decision making - Hughes, Wayne P.; Bryson, Marion R. (Military Operations Research Society, 1997)
A collection of papers that explore of the use of modeling in military planning. Explores how modeling applies to a variety forms of military engagement including ground, sea, air and nuclear warfare.